A new digital approach to design 3D CAP waveforms. - Xiaosong Tang
A minimax optimization approach has previously been contributed to extend the conventional two-dimensional (2D) carrierless amplitude/phase modulation (CAP) scheme to three-dimensional (3D) (see Shalash, A. and Parhi, K.K., IEEE Trans. Commun., vol.47, p.1655-67, 1999; Proc. IEEE ISCAS '97, p.2136-9, 1997). We show that there is no guarantee of spectral efficiency by this approach. This is a potentially fatal design flaw which results in the 3D CAP system being exceptionally susceptible to noise, even if it is of very small magnitude, for example, quantization noise. A new minimax approach is, thus, contributed to design bandwidth-efficient 3D CAP waveforms which are more robust and useful for very high-speed digital subscriber loop applications and high-speed LAN systems. Some design examples are provided.
Keywords: 3D waveforms; Amplitude modulation; Carrierless amplitude/phase modulation; Digital subscriber loop; High-speed LAN; Minimax optimization; Phase modulation; Quantization noise; Spectral efficiency